Abortion decision-making attitudes of adolescents attending Roman Catholic schools - Crock, Rosemary J. (Kansas State University, 2007)
This exploratory study examines abortion decision-making attitudes of adolescents attending Roman Catholic schools. With a theoretical background using both cognitive-developmental theory and moral development theory, this study investigated adolescent abortion decision-making attitudes with a multi-part paper and pencil survey. The first part of the Abortion Attitude Scale consisted of a combination of the seven General Social Survey (GSS) abortion questions, intermingled with seven additional author-devised abortion questions. The second part of the survey consisted of sixteen reality-based scenarios, each containing a high or low level of four dimensions. The dimensions consisted of the four most common reasons for abortion females wrote about in their online written testimonies about their actual abortion experiences. The four dimensions were determined after the author conducted a frequency count of reasons for abortion originating from 87 testimonies from pro-choice web sites and 82 testimonies from pro-life web sites, plus phone calls to 8 pro-choice agencies and phone calls to 8 pro-life agencies. The Abortion Attitude Scale was offered to a convenience sample of 8th through 12th graders attending the Topeka, Kansas Catholic Schools, which includes five elementary schools and one high school. Written parental consent and written student ascent were required for students to be eligible to participate in the study. A total of 350 students participated. The study’s six hypotheses explored whether or not the combined GSS and author-devised abortion questions are unidimensional; whether or not interaction effects exist among the four dimensions in each of the scenarios; and how the independent variables of gender, age, ethnicity, and intrinsic religiosity may impact adolescents’ abortion attitudes. Results suggest several conclusions. The GSS and author-devised abortion questions are multidimensional. Regarding the four dimensions used in each of the scenarios, there were interaction effects among the four dimensions. Whereas the adolescent female participants in this study did appear to be less accepting of abortion than the male participants, and the adolescents with higher intrinsic religiosity appeared to be less accepting of abortion, the hypotheses regarding younger age and greater ethnic diversity did not appear to lend support to adolescents being less accepting of abortion. The findings thus appear to show that this study’s participants had complex attitudes about abortion decision-making, and that these attitudes appear to be at least somewhat situationally-dependent. Implications for further studies are discussed, along with limitations and conclusions.
Keywords: Abortion; Decision-making; Attitudes; Adolescents; Catholic; Schools; Education, Social Sciences (0534); Religion, General (0318); Sociology, Individual and Family Studies (0628)